Physiological signal analysis for cognitive state estimation - Mohiuddin, Ahmad; Atiqul, Islam; Khan Munia, T. T.; Mohd Abdur, Rashid; Tunku Muhammad Nizar, Tunku Mansur (World Scientific Publishing Co., 2013)
Link to publisher's homepage at http://www.worldscientific.com/